Pengaruh konservatisme akuntansi dan leverage terhadap tax avoidance dengan kepemilikan institusional sebagai variabel moderasi - Margareth Vionika; Juanda Astarani; Khristina Yunita (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study examines and analyzes accounting conservatism and the power to avoid taxes with institutional ownership as a moderating variable. This sample includes manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange from 2020 to 2023. This study includes 37 companies that meet the sample criteria. The analytical method is multiple linear regression analysis, and the analytical tool is SPSS 25. This research indicates that accounting conservatism does not influence efforts to avoid taxes; power influences efforts to avoid taxes; institutional ownership cannot control accounting conservatism to avoid taxes, and institutional ownership can weaken the power used to avoid taxes. Public interest statements The study provides valuable insights for corporate managers, investors, and policymakers regarding the interplay between accounting practices, tax strategies, and ownership structures. By understanding these dynamics, stakeholders can make more informed decisions that align with their financial and ethical objectives.